Interpersonality in Legal Genres - Breeze, Ruth (Peter Lang AG, Internationaler Verlag der Wissenschaften, 2014)
Few concepts in Discourse Studies are so versatile and intricate and have been so frequently contested as interpersonality. This construct offers ample terrain for new research, since it can be viewed using a range of diverse theoretical frameworks, employing a variety of analytical tools and social perspectives. Studies on the relationship between writer/reader and speaker/audience in the legal field are still scarce, dispersed, and limited to a narrow range of genres and a restricted notion of interpersonality, since they are most often confined to modality and the Gricean cooperative principles. This volume is meant to help bridge this gap. Its chapters show the realisation and distribution of interpersonal features in specific legal genres. The aim is to achieve an expansion of the concept of interpersonality, which besides modality, Grice's maxims and other traditionally interpersonal features, might comprise or relate to ideational and textual issues like narrative disclosure, typography, rhetorical variation, or Plain English, among others
Description based on publisher supplied metadata and other sources
Keywords: Recht; Interpersonal relations; Law -- Language; Psycholinguistics; Rhetoric; Sublanguage; Rechtssprache; Interpersonale Kommunikation; Aufsatzsammlung